Pengaruh Dimensi E-Government Quality Terhadap Kepuasan Masyarakat Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Tanah Bumbu - Muhammad Taufik Mufin; Sitna Hajar Malawat; Junaidy Junaidy; Devia Hetty Hernany (Journal on Education, 2024)
This research aims to analyze the influence of the E-Government Quality Dimension on community satisfaction with the Population and Civil Registration Services of Tanah Bumbu Regency.This research is quantitative with a correlational approach. The population in this research is all people who receive services from the Tanah Bumbu Regency Population and Civil Registration Service. The total sample was 140 people and the sampling technique used was random sampling. Data was collected through questionnaires and documentation and then analyzed using multiple linear regression.The research results show that the E-Government Quality Dimension has a positive and significant influence on community satisfaction with the Tanah Bumbu Regency Population and Civil Registration Service, both partially and simultaneously.